2018
DOI: 10.4049/jimmunol.1700540
|View full text |Cite
|
Sign up to set email alerts
|

TLR2 Stimulation Strengthens Intrahepatic Myeloid-Derived Cell-Mediated T Cell Tolerance through Inducing Kupffer Cell Expansion and IL-10 Production

Abstract: Hepatic APCs play a critical role in promoting immune tolerance in the liver. Recently, we have demonstrated that TLR2 stimulation on liver sinusoidal endothelial cells reverted their suppressive properties to induce T cell immunity. However, there is a paucity of information about how TLR2 stimulation modulates the immunological function of other hepatic APCs. In the current study, we investigated whether TLR2 stimulation influences the function of intrahepatic myeloid-derived cells (iMDCs) and elucidated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 52 publications
1
40
3
2
Order By: Relevance
“…We previously showed that TLR2 activation may also modulate the immune functions of intrahepatic liver sinusoidal endothelial cells (LSECs) ( 32 ). However, we further found that intrahepatic KCs retained the tolerizing activity after TLR2 activation and even increased the IL-10 production ( 33 ). Thus, the recruitment of immune cells into the liver, especially macrophages, may be essential to support T cells as effector cells against HBV ( 20 ).…”
Section: Discussionmentioning
confidence: 93%
“…We previously showed that TLR2 activation may also modulate the immune functions of intrahepatic liver sinusoidal endothelial cells (LSECs) ( 32 ). However, we further found that intrahepatic KCs retained the tolerizing activity after TLR2 activation and even increased the IL-10 production ( 33 ). Thus, the recruitment of immune cells into the liver, especially macrophages, may be essential to support T cells as effector cells against HBV ( 20 ).…”
Section: Discussionmentioning
confidence: 93%
“…A direct interaction between HBsAg and KCs with HBsAg uptake, was documented both in vitro and in ex vivo isolated KCs from CHB patients (129). In vitro exposure to HBV antigens preferably induced TGF-β, rather than pro-inflammatory cytokine secretion by primary rat KCs (130); moreover, HBV antigen interaction with TLR2 on KCs caused T cell inhibition through IL-10 secretion (131,132) and TLR2 knockout or KC depletion resulted in enhanced HBV elimination and improved CD8+ T cell responses in mice (131). This inhibitory effect mediated by HBV proteins was further documented by more recent studies showing that HBV protein uptake by intrahepatic macrophages from CHB patients can favor anti-inflammatory over pro-inflammatory functions and can ultimately promote hepatocyte infection (133).…”
Section: Tolerogenic Apcmentioning
confidence: 98%
“…Beyond both TLR-and TNF-signaling pathways during MAP infection, the classical NFκβ negative feedback system, as schematized in Figure 5, can also induce tolerance. While the endotoxin tolerance is generally mediated by TLR4, other microbial products can stimulate receptors such as TLR2 (116) or TNF receptor (117) to induce crosstolerance. TNF selectively diminished cytokine production in response to subsequent endotoxin challenge (118).…”
Section: Immune Tolerance In Perspective To Explain Refractory State mentioning
confidence: 99%